Gazing at the Crystal Ball: Predicting the Future of Marine Protected Areas Through Voluntary Commitments - Nocito, Emily S.; Brooks, Cassandra M.; Strong, Aaron L. (Frontiers in Marine Science, 2020)
2015 saw a new era within the United Nations: the era of the Sustainable Development Goals. Built off the previous Millennium Development Goals, this new set of goals was expanded to 17 target areas. Fast forward to June 2017, at the United Nation’s Headquarters in New York City, a high-level conference surrounding Sustainable Development Goal (SDG) 14: Life Under Water convened. One aspect of goal 14 calls for 10% of the ocean conserved by the year 2020, through sub-target 14.5. That 10% fulfillment is often thought of in terms of marine protected areas (MPAs). While many objectives were laid out for this conference, one of the most prominent objectives was to build on existing partnerships and foster new collaborations. One way to achieve this target was through the creation of the voluntary commitment program. This “Call for Action” came from the heads of state and government, as well as high-level representatives from organizations and stakeholder groups. Under this “Call for Action”, twenty-two actions related to goal 14 were listed for stakeholders to partake in, including an appeal to create voluntary commitments surrounding the oceans. As of September 2017, 1,395 voluntary commitments were registered through the voluntary commitment portal process, spanning across organizations and disciplines. Here, we analyze these commitments, specifically those related to the fifth sub-target of SDG 14. Commitments were further refined through the focus on those under 14.5 that focused on different forms of resilience, resulting in 133 separate codes over 12 forms of resilience. Through analyzing commitments, we map out future plans and reveal different forms of marine protected areas. This research shows collaboration and co-production of knowledge linking across the SDGs. This work can be seen as a stepping-stone to the fulfillment of 10% conservation by 2020.